Aryl hydrocarbon receptor negatively regulates lipid synthesis and involves in cell differentiation of SZ95 sebocytes in vitro. (25th October 2016) - Hu, Tingting; Wang, Duo; Yu, Qian; Li, Li; Mo, Xiaohui; Pan, Zhanyan; Zouboulis, Christos C.; Peng, Luying; Xia, Longqing; Ju, Qiang
Abstract: The aryl hydrocarbon receptor (AhR) is the receptor for 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), benzo(a)pyrene (BaP) and other exogenous compounds. In human sebocytes, TCDD and BaP were found to activate the expression of multiple genes, including cytochrome P450 1A1 (CYP1A1), and inhibit lipid synthesis via AhR, while little is known about endogenous functions of the AhR. In order to expand this knowledge, we analyzed the impact of AhR knockdown on lipid synthesis as well as on cell differentiation of SZ95 sebocytes in vitro and observed that lipid synthesis was significantly induced in AhR silenced SZ95 sebocytes. In line with this result, expression of lipogenesis-associated genes, such as peroxisome proliferator activated receptor (PPAR) δ and PPARγ, was increased. Morphological changes with smaller cells in size but more abundant cytoplasmic lipids were observed in AhR silenced SZ95 sebocytes compared with the AhR activated cells. Besides, the expression of keratin 7, an early sebaceous differentiation marker, was increased, while the expression of the terminal sebocyte differentiation marker epithelial membrane antigen (EMA) was reduced. Moreover, the terminal keratinocyte differentiation markers keratin 10 and involucrin, and the AhR downstream protein CYP1A1 were reduced after AhR silencing. To the best of our knowledge, we provide evidence that in the absence of exogenous ligands, the AhR inhibits lipid synthesis and involves in cell differentiation of human SZ95 sebocytes, which indicates the physiological function of this receptor in human sebocytes. Highlights: The lipid synthesis was induced after AhR silence in SZ95 sebocytes. AhR silenced SZ95 sebocytes were prone to be small with more cytoplasmic lipids. Antigen expression of differentiation in sebocytes was altered after AhR silence. Sebocyte differentiation was promoted with a premature status after AhR silence.